Assessment of The Prevalence and Associated Risk Factors of Gastrointestinal Parasite of Goats in Afgooye District, Lower Shabelle, Somalia - Moktar Omar Sheikh Mohamed; Abdisalam Mohamed Ibrahim; Hawakin Abdirizak Ahmed; Mohamud Abdislam Yusuf Yusuf; Jeilani Busuri Mio; Omar Mohamud Salah; Zainab Mohamed Abdirahman; Yasin Hussein Sh Hassan (Journal of Applied Veterinary Science And Technology, 2023)
Background: Gastrointestinal parasitic diseases remain an obstacle to goat farmers in Somalia and worldwide. Purpose: This study aimed to determine the prevalence and associated risk factors of gastrointestinal parasites in goats in the Afgooye district, Lower Shabelle region, Somalia. Methods: To fulfill this study, an examination of 384 fecal samples of goats kept by smallholders was conducted. The results were achieved during the period from August 2020 to January 2022. Results: The examination of fecal samples revealed that the overall prevalence of gastrointestinal parasitic infections among goats was 71.61%. The data analysis conducted during the study indicated that there is no significant association (P > 0.05) between goat districts and gastrointestinal (GI) parasite infection. The corresponding percentage of gastrointestinal parasites in males and females was 70% and 72%, respectively. However, these variables were not significantly associated (p-value = 0.399). After categorization, age was not significantly associated with the parasitic infection status of the animal. The common parasitic infections prevalent were Nematode, Trematode, Cestode, and Protozoa types were found in different numbers. According to the flotation and sedimentation techniques, Eimeria sp. (29%) was found with higher prevalence followed by Haemonchus sp. (23%), Trichostrongylus sp. (11%), Moniezia sp. (10%), Trichuris sp. (9%), Strongyloides sp. (7%), Dictyocaulus sp. (5.2%), Nematodirus (4%), and least was Fasciola sp. (1.0%). Conclusion: This study provides comprehensive documentation on multiple GI parasites among goats in the Afgooye district, Lower Shabelle region of South-western State, Somalia, and the findings are crucial for effective farm management, especially for formulating the effective GI parasitic control vis-a-vis novel elimination strategies.